The Effect Of Health Promotion With Social Media Tiktok On Increasing Knowledge And Attitude Change In Preventing Hypertension Early On In Adolescents In Smk Negeri 1 Jambi City - Satifa Dayanti Putri; Silvia Mawarti Perdana; Puspita Sari; M. Ridwan; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2025)
Hypertension is a non-communicable disease whose prevalence is increasing, including among adolescents. Low knowledge and preventive attitudes are factors that contribute to the high incidence. Social media, especially TikTok, as a platform favored by adolescents, can be used as an effective and attractive health promotion media. This study used a pre-experimental design with a one group pretest posttest approach. The sample consisted of 95 students of SMK Negeri 1 Kota Jambi who were selected using a purposive sampling technique. The intervention was carried out through the delivery of educational videos about hypertension through the TikTok platform. Data collection was carried out using a knowledge and attitude questionnaire given before and after the intervention. Data analysis used Wilcoxon signed rank tests. The results of the analysis showed a significant increase in the knowledge and attitude scores of respondents after being given educational intervention through TikTok with a p-value <0.05. This shows that the use of TikTok social media is effective in increasing knowledge and forming positive attitudes of adolescents in preventing hypertension early on. Health promotion through TikTok social media has proven effective in increasing knowledge and changing adolescent attitudes towards early prevention of hypertension. TikTok's interactive and easily accessible media is a relevant and interesting educational tool for adolescents, so it can be used as an innovative health promotion strategy in efforts to prevent non-communicable diseases such as hypertension.